2014
DOI: 10.1007/s11999-014-3613-y
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions After Surgical Treatment of Proximal Humerus Fractures: Is Arthroplasty Safer Than Open Reduction Internal Fixation?

Abstract: Background With technologic advances such as locked periarticular plating, hemiarthroplasty of the humeral head, and more recently reverse total shoulder replacement, surgical treatment of proximal humerus fractures has become more commonplace. However, there is insufficient information regarding patient outcomes after surgery, such as the frequency of unplanned hospital readmissions and factors contributing to readmission. Questions/purposes We measured (1) the frequency of unplanned hospital readmissions aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…13 These data have been used in previous studies evaluating trends in hospital readmissions among children 14 and adults. 15,16 We obtained data for live births in New York State from the New York Department of Health (http://www.health.ny.gov/statistics/vital_statistics/). Because the analysis was of de-identified data, it was considered exempt for human subjects review by the Vanderbilt University School of Medicine Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…13 These data have been used in previous studies evaluating trends in hospital readmissions among children 14 and adults. 15,16 We obtained data for live births in New York State from the New York Department of Health (http://www.health.ny.gov/statistics/vital_statistics/). Because the analysis was of de-identified data, it was considered exempt for human subjects review by the Vanderbilt University School of Medicine Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining preoperative demographic and surgical variables identified on univariate analysis were no longer significant on multivariate analysis after controlling for the influence of the remaining risk factors. In contrast, the role of patient factors and surgical characteristics in hospital readmission after TSA in single-state [24][25][26] or single-institution investigations 21 is limited because these studies did not provide the same level of detail on medical comorbidities, laboratory values, and surgical characteristics as the NSQIP data set. Additionally, the current study found no difference for factors previously shown to predict increased 60-to 90-day readmission rates after TSA, such as age, 25 race, 26 or increasing number of medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Medical complications rather than surgical complications were responsible for most readmissions after TSA, and this finding corroborates previous studies that showed that 80% to 82% of complications leading to readmission after TSA were medical. 25,26 The identification of pertinent complications that contribute to hospital re- admission after primary TSA can lead to targeted interventions to mitigate these complications in high-risk patients during the perioperative period. In the absence of reliable evidence, the American Academy of Orthopaedic Surgeons offered a consensus statement advocating for perioperative mechanical or chemical venous thromboembolic prophylaxis for patients undergoing TSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 40% of the complications are seems to be related to the incorrect surgical technique that is mostly related to the experience [4]. Because of high complication rates in 4-part fractures, some authors recommend hemiarthroplasty to avoid seconder surgery despite to lower functional outcomes than locking plates [16,25]. Patient's age negatively affects the functional results that are managed with osteosynthesis [6,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%